Association Between Visceral Fat and Monocyte Count in Type 2 Diabetes Mellitus: Evidence from a Referral Hospital Study - Henhen Heryaman; Alfi Alfisa Aji; Maya Kusumawati (Biology, Medicine, & Natural Product Chemistry, 2025)
The majority of patients with type 2 diabetes mellitus (T2DM) exhibit central obesity. Central obesity is characterized by an abnormally high accumulation of visceral adipose tissue. Individuals with both obesity and T2DM often present with additional immune dysfunction, including significantly elevated monocyte counts compared to metabolically healthy obese individuals. A recent study has demonstrated a correlation between visceral fat and monocyte count in young adults with obesity; however, this association remains unclear in patients with T2DM. A cross-sectional observational study was conducted using a total sampling design from August to September 2022 at AMC Hospital, Indonesia. History taking, physical examination, and laboratory examination were conducted. Visceral fat, monocyte count, and confounders (age, gender, diagnosis duration of T2DM, glycemic control (using FBG), BMI, WC, number of comorbidities, and number of drug use) were observed. In the complete sample (n = 57), after adjusting for confounding variables, there was no statistically significant association between visceral fat and monocyte count (adjusted ? = 86.635, 95% CI [–19.050, 192.321], P = 0.106). However, after excluding one influential subject and controlling for confounders, a significant association was observed (adjusted ? = 110.023, 95% CI [11.111, 208.935], P = 0.030). There was a significant association between visceral fat and monocyte count in T2DM.